The Effect of Plyometric Training Before and After Technical Training on Smash Ability of Male Volleyball Athletes - Permana, Hendri; Sukamti, Endang Rini; Suhadi, Suhadi; Prabowo, Trisnar Adi (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
The purpose of this study was to analyze the effect of plyometric training before and after smash technique training. This type of research is an experiment with a two group, the two groups are the plyometric group before technique training (BTT) and the plyometric group after technique training (ATT). The sample was 20 male and age 18-19 years, then grouped through ordinal pairing. The training program was carried out for 6 weeks with 18 meetings. Plyometric training program: squats, sit-ups, fence jumping, push-ups, up and down the bench, back-up, skipping, jack kneef, shuttle run, stabilization, sedo smash, step and shoulder. The program is 8 – 10 repetitions, 2 – 3 sets, recovery between sets 2 – 3 minutes, intensity 85% - 95%. Meanwhile, the smash technique training program is a drill accompanied by a coach with a total duration of 60 minutes. Data collection for smash skills as a pretest-posttest using the Stanley test. The t-test result (p<0.05), ATT shows Sig. 0.002, than BTT Sig. 0.078. Independent t-test (p<0.05) also shows that there is a difference between BTT and ATT is Sig. 0.042. Conclusion is placing plyometric training after a smash technique training session (ATT) is more effective in improving smash ability for male volleyball athletes aged 18-19 years. This study recommends scheduling plyometrics after technique training as a more optimal strategy, supporting better athletic performance and efficient recovery, while minimizing the risk of injury and fatigue.